Germanyl triazoles as a platform for CuAAC diversification and chemoselective orthogonal cross-coupling - John M. Halford-McGuff; Thomas M. Richardson; Aidan P. McKay; Frederik Peschke; Glenn A. Burley; Allan J. B. Watson (Beilstein Journal of Organic Chemistry)
We report the synthesis of germanyl triazoles formed via a copper-catalysed azide–alkyne cycloaddition (CuAAC) of germanyl alkynes. The reaction is often high yielding, functional group tolerant, and compatible with complex molecules. The installation of the Ge moiety enables further diversification of the triazole products, including chemoselective transition metal-catalysed cross-coupling reactions using bifunctional boryl/germyl species.